Modified rammed earth material as well as preparation method and application thereof
By adding specific content of blending materials to traditional rammed earth materials, modified rammed earth materials are prepared, which solves the problem of poor performance of traditional rammed earth in humid and hot environments, and has achieved significant improvement in mechanical properties and durability. It is suitable for rammed earth materials in extreme environments.
Patent Information
- Application Number
- CN202510090114.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
AI Technical Summary
Traditional rammed earth materials are prone to peeling and peeling in humid and hot environments, resulting in poor mechanical properties and durability, limiting their application range.
Modified rammed earth materials are prepared by mixing specific contents of blending materials (such as volcanic ash, brick powder, fly ash) with yellow mud, sand, ripe lime, oyster shell ash, glutinous rice flour and yellow sugar water to adjust their performance.
Modified rammed earth materials have significantly improved in terms of mechanical properties (compressive strength, microstructure) and durability (water impregnation resistance, salt corrosion resistance, water permeability), and are suitable for rammed earth materials in extreme weather and climate change.
Smart Images

Figure CN119899011A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building material preparation, and in particular to a modified rammed earth material and a preparation method and application thereof. Background Art
[0002] Modified rammed earth is a building material that improves the performance of traditional rammed earth by adding improved materials. This improvement process aims to solve some inherent problems of traditional rammed earth, such as water resistance, low strength and poor volume stability. Traditional rammed earth has poor mechanical properties and durability, especially in a long-term hot and humid environment, it is very easy to peel and flake, which greatly limits the application of rammed earth.
[0003] In view of this, it is necessary to design an improved modified rammed earth material and a preparation method and application thereof to solve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a modified rammed earth material and a preparation method and application thereof.
[0005] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a modified rammed earth material, comprising the following raw materials in parts by volume:
[0006] 45 parts of yellow mud, 12 parts of sand, 7 parts of slaked lime, 2 parts of oyster shell ash, 1 part of glutinous rice flour, 5-15 parts of admixtures and 20% by mass of brown sugar water;
[0007] The admixture is at least one of volcanic ash, brick dust and fly ash.
[0008] Preferably, when the admixture is pozzolan, its volume is 5-15% of the volume of all raw materials.
[0009] Preferably, when the admixture is brick powder, its volume is 5-15% of the volume of all raw materials.
[0010] Preferably, when the admixture is fly ash, its volume is 5-15% of the volume of all raw materials.
[0011] Preferably, the volume of the volcanic ash is 10% of the volume of all raw materials.
[0012] Preferably, the volume of the brick powder is 5% of the volume of all raw materials.
[0013] Preferably, the volume of the fly ash is 15% of the volume of all raw materials.
[0014] On the other hand, the present invention also provides a method for preparing the modified rammed earth material, comprising the following steps:
[0015] The following raw materials are mixed evenly in volume: 45 parts of yellow mud, 12 parts of sand, 7 parts of slaked lime, 2 parts of oyster shell ash, 1 part of glutinous rice flour, 5-15 parts of admixtures and an appropriate amount of 20% by mass of yellow sugar water to obtain modified rammed earth material; wherein the admixture is at least one of volcanic ash, brick powder and fly ash.
[0016] Preferably, when the admixture is pozzolan, its volume is 5-15% of the volume of all raw materials; when the admixture is brick powder, its volume is 5-15% of the volume of all raw materials; when the admixture is fly ash, its volume is 5-15% of the volume of all raw materials.
[0017] In particular, the modified rammed earth material prepared by the above preparation method can be applied to the field of rammed earth construction.
[0018] The beneficial effects of the present invention are:
[0019] 1. The modified rammed earth material provided by the present invention is prepared by mixing a specific content of admixtures with yellow mud, sand, slaked lime, oyster shell ash, glutinous rice flour and yellow sugar water. By adjusting the type and amount of the admixtures, the performance of the modified rammed earth material can be precisely controlled, and finally a modified rammed earth material with improved mechanical properties (compressive strength, microstructure) and durability (water immersion resistance, salt corrosion resistance, water permeability) is obtained.
[0020] 2. The modified rammed earth material provided by the present invention has the best performance when the admixture is 5% brick powder, or 10% volcanic ash, or 15% fly ash by volume. After adding the above admixtures, the performance of the modified material is greatly improved, especially the compressive strength and water permeability, and is therefore more suitable as a rammed earth material for use in extreme weather and climate change processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the structure of the mold used in the present invention;
[0022] Figure 2 for Figure 1 A top view of
[0023] Figure 3 The compressive strength test results of the test blocks prepared from Examples 1-9 of the present invention and the control sample;
[0024] Figure 4 The SEM images of the test blocks prepared in Examples 1-9 of the present invention;
[0025] Figure 5 This is the SEM image of the control sample;
[0026] Figure 6 The test steps for the water immersion resistance test of the present invention;
[0027] Figure 7 The water immersion resistance test results of the present invention;
[0028] Figure 8 This is a graph showing the water absorption performance of the modified rammed earth material of the present invention;
[0029] Fig. 9 The changes in water absorption and evaporation of the modified rammed earth material of the present invention per unit time at different time periods;
[0030] Fig.10 FIG. 1 is a diagram of a test device for water permeability testing of the present invention;
[0031] Fig.11 The results of the change of water permeability per unit area of the test blocks prepared from Examples 1-9 of the present invention and the control sample are shown;
[0032] Fig.12 The test steps for the salt corrosion resistance test of the present invention are as follows;
[0033] Fig.13 This is a salt analysis state diagram of the 6th test block of the salt corrosion resistance test of the present invention;
[0034] Fig.14 This is a salt analysis state diagram of the 8th day control sample of the salt corrosion resistance test of the present invention;
[0035] Fig.15 This is a salt analysis state diagram of the 12th test block of the salt corrosion resistance test of the present invention;
[0036] The reference numerals are as follows:
[0037] 1. Rammer; 2. Through hole; 3. First fixed seat; 4. Fixed bracket; 5. Force hammer; 6. Mould; 7. Second fixed seat. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0039] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0040] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0041] The modified rammed earth material provided by the present invention comprises the following raw materials in parts by volume: 45 parts of yellow mud, 12 parts of sand, 7 parts of slaked lime, 2 parts of oyster shell ash, 1 part of glutinous rice flour, 5-15 parts of admixtures and an appropriate amount of yellow sugar water with a mass fraction of 20%, wherein the admixture is at least one of volcanic ash, brick powder and fly ash; when the admixture is volcanic ash, its volume is 5-15% of the volume of all raw materials; when the admixture is brick powder, its volume is 5-15% of the volume of all raw materials; when the admixture is fly ash, its volume is 5-15% of the volume of all raw materials.
[0042] Furthermore, the present invention provides a method for preparing the modified rammed earth material, comprising the following steps: uniformly mixing the following raw materials by volume: 45 parts of yellow mud, 12 parts of sand, 7 parts of slaked lime, 2 parts of oyster shell ash, 1 part of glutinous rice flour, 5-15 parts of admixtures and an appropriate amount of 20% yellow sugar water by mass, to obtain the modified rammed earth material, wherein the admixture is at least one of volcanic ash, brick powder and fly ash. The modified rammed earth material prepared by the above method exhibits excellent mechanical properties (compressive strength, microstructure) and durability (water immersion resistance, salt corrosion resistance, water permeability), has strong applicability and feasibility in the field of rammed earth construction (such as interior decoration, building structure, landscape design, etc.), and is of great significance to the sustainable development of rammed earth construction.
[0043] The modified rammed earth material and its preparation method and application proposed by the present invention are further described below in conjunction with specific embodiments:
[0044] Examples 1-9
[0045] Example 1-9 provides a modified rammed earth material, which includes the following raw materials in volume: 45 parts of yellow mud, 12 parts of sand, 7 parts of slaked lime, 2 parts of oyster shell ash, 1 part of glutinous rice flour, 5-15 parts of admixtures and an appropriate amount of 20% by mass of brown sugar water, wherein the admixture is at least one of volcanic ash, brick powder, and fly ash. It should be noted that the amount of brown sugar water added is 170-200 mL. In actual application, the specific amount added can be determined according to the amount of all solid raw materials added, as long as all solid raw materials can be ensured to be evenly mixed.
[0046] After mixing the various raw materials evenly according to the raw material formula, a modified rammed earth material is obtained, and a test block is made with the modified rammed earth material as the raw material. The specific preparation method is as follows: the modified rammed earth material is placed in a homemade mold, about 20 mL of soil is added each time, and a laboratory-modified ramming instrument is used to tamp the soil with a rammer 1 at a height of 30 cm by free fall, and each layer is tamped 50 times. The above steps are repeated layer by layer. In a single test, three parallel controls are set for rammed earth test blocks with different proportions. The conditions for the test block preparation process are: temperature 20-25°C, and ambient humidity 55-65%.
[0047] Further, the structural schematic diagram of the self-made mold used in the above process is as follows Figure 1 As shown, the top view is Figure 2 As shown, the homemade mold includes a circular first fixed seat 3 and a second fixed seat 7, which are connected by a number of fixed brackets 4. The first fixed seat 3, the second fixed seat 7 and all the fixed brackets 4 together form a space for tamping the soil, in which a mold 6 is provided; specifically, the homemade mold also includes a rammer 1, and the first fixed seat 3 is provided with a through hole 2. The rammer 1 passes through the through hole and extends to the inside of the tamping soil space, and a force hammer 5 is provided at the end of the rammer 1. The force hammer 5 is located directly above the mold and close to the mold. The central axes of the first fixed seat 3, the second fixed seat 7, the force hammer 5 and the mold 6 are all in a straight line.
[0048] According to the difference in the type and content of the test block admixtures, the test samples of Examples 1-9 are numbered respectively, and the specific sample numbers are shown in Table 1. The test blocks are demoulded and placed in a Q-SUN test box. The test blocks are cured in dark conditions with a relative temperature of t=25±1°C and a relative humidity of RH=50±2%. The curing cycle is 20 days, during which the weight of the test blocks is weighed and recorded every 24 hours using an electronic balance. The Q-SUN test box parameter settings during the curing period are shown in Table 2. During the test, the conditions in Table 2 are used as standard curing conditions. It should be noted that the volume ratio in Table 1 is the ratio of the volume of the corresponding admixture to the total volume of the test block raw materials under this condition.
[0049] Table 1 Amount of admixture added in Examples 1-9
[0050] project Type of admixture Volume ratio (%) Sample No. Control none 0 OR-00 Example 1 Brick powder 5 BR-05 Example 2 Brick powder 10 BR-10 Example 3 Brick powder 15 BR-15 Example 4 Volcanic ash 5 CI-05 Example 5 Volcanic ash 10 CI-10 Example 6 Volcanic ash 15 CI-15 Example 7 Fly ash 5 FL-05 Example 8 Fly ash 10 FL-10 Example 9 Fly ash 15 FL-15
[0051] Table 2 Q-SUN equipment parameters during the curing period of the test block
[0052] Environmental indicators Setting parameters Lighting environment dark Irradiance(W / ㎡) 0.00 Temperature(℃) 25±1 RH(%) 50±2 Step duration (h) 99 Test duration (h) 480
[0053] Compressive strength test:
[0054] After 20 days of curing under standard curing conditions, the test block was taken out and the compressive strength test was carried out using a universal material testing machine. The test block size was a cube of 50×50×50mm. The test speed of the universal material testing machine was 1.000mm / min and the test stress rate was 0.005(kN / mm 2 ) / s, the upper limit of stress is 0.2kN / mm 2 The test was terminated when the test block was uniformly loaded until failure was detected. The test results are shown in Table 3 and Figure 3As shown in the table, it can be seen that in terms of the compressive strength of rammed earth, when the brick powder addition amount is 5%, the small particles fill the gaps between the large aggregates and improve the density inside the test block. Compared with the control sample, the compressive strength of the test block tends to increase, but with the increase in the amount of brick powder added, the water absorption property of the material itself causes the water retention property of the test block to deteriorate with the increase in the amount of addition, and the compressive strength decreases accordingly; when the admixture is volcanic ash or fly ash, the compressive strength of the test block of the former shows a weakening trend with the increase of its content, while the compressive strength of the test block of the latter gradually increases with the increase of its content, and when the volcanic ash addition amount is 5% or the fly ash addition amount is 15%, the compressive strength is significantly improved compared with the control sample, which are 10.020 and 10.800MPa respectively.
[0055] Table 3 Compressive strength test results of test blocks of Examples 1-9
[0056]
[0057] Microstructure Analysis:
[0058] The SEM images of the test blocks prepared in Examples 1-9 are as follows: Figure 4 As shown in the figure, it can be seen that with the increase of brick powder and volcanic ash addition, the density of the test block structure becomes worse, the internal bonding force of the test block decreases, and when the test block is subjected to force, it will continue to expand along the gap, causing the structure to break. The cross-sectional SEM shows more needle-shaped and flaky structures. This result is more obvious in the test block with brick powder as the admixture; when fly ash is used as an admixture, although there are still a few cracks in the cross-sectional SEM, the bonding property of the material makes the internal structure of the test block more uniform and the density increases. The mechanical properties of the improved test block increase with the increase of content; the SEM images of the control sample (without adding admixture) at different magnifications are shown in Figure 5 As shown in the figure, it can be seen that there are more needle-shaped crystals and fine particles in the SEM image of the test block section, and obvious cracks can be seen. The parameters of the SEM test process are: the pressure value of the electron microscope chamber is 50Pa, the test voltage is 15.0kV, the test current is 29μA, and the observation is made under 500 times and 1000 times respectively.
[0059] Water resistance test:
[0060] The test block with a size of 50×50×50mm was taken out for testing after being cured for 20 days under standard curing conditions. The test was carried out as follows: the test block was immersed in pure water so that the area below the height of 5mm of the test block was immersed in water, and photos were taken to record the water absorption of the test block when the immersion time of the test block was 20min and 30min. After immersion for 24h, the test block was placed in a natural environment (temperature is about 22±2℃, ambient humidity is about 60±4%) for natural evaporation for 3d, and the immersion for 24h and natural evaporation for 3d steps were repeated 6 times (one cycle means that the test block is immersed in water for 24h and then evaporated for 3d). Parallel samples were carried out simultaneously in the same environment. The experimental steps are shown in Figure 6 , the specific test results are as follows Figure 7 As shown, Figure 7 It is the water absorption rate per unit time of the test blocks of Examples 1-9 and the control sample. It can be seen from the figure that when brick powder is used as an admixture, the higher its content, the faster the water absorption rate of the test block, among which the water absorption rate of the test block with 15% brick powder addition is not much different from that of the control sample; when volcanic ash and fly ash are used as admixtures, the higher the admixture content, the slower the water absorption rate of the test block when immersed in water. Among them, the blue dotted line in the figure is the boundary of water penetration during the water absorption process of the test block.
[0061] Figure 8 a is the water absorption of the test block per unit time. It can be seen from the figure that the water absorption of the test block with 5% brick powder addition is less than that of the control sample, but the water absorption of the test blocks with 10% and 15% brick powder addition is higher than that of the control sample; when volcanic ash is added to rammed earth as an admixture, there is no obvious difference in the water absorption mass per unit time with the increase of its content; when fly ash is used as an admixture, the water absorption mass per unit time is significantly reduced compared with rammed earth test blocks with any other formula, especially when the fly ash addition is 15%, the water absorption mass per unit time is only 1 / 4 of that of the control sample.
[0062] Figure 8 b is the extreme value of water absorption in saturated state. It can be seen from the figure that the water absorption of the test block with brick powder as admixture in saturated state shows an upward trend with the increase of its content, but the water absorption of the test block with 5% brick powder addition is lower than that of the control sample; the water absorption of the test block with volcanic ash as admixture in saturated state has little to do with its addition amount and is lower than that of the control sample; and the water absorption of the test block with fly ash as admixture in saturated state is negatively correlated with its addition amount, and the difference is large.
[0063] Fig. 9 In order to modify the changes in water absorption and evaporation of rammed earth materials per unit time in different periods, by comparing the changes in water absorption and evaporation between test blocks with different admixtures, it was found that the test blocks made with 15% fly ash addition had the best various water resistance performance indicators.
[0064] Water permeability test:
[0065] The test block with the size of 100×100×20mm (length×width×height) was taken out for testing after being cured for 20 days under standard curing conditions. The water permeability test was carried out as follows: pure water was injected into the culture dish, the test block was placed on the edge of the culture dish, and glass glue was applied to the area on the side of the culture dish that was in contact with the test block to fix the test block on the top of the culture dish. Then, the vertical area of the test block with a height of 20mm was fully coated with glass glue to ensure that the water in the crystallization dish could only pass through the circular area at the bottom of the test block and the rectangular area at the top. The size of the crystallization dish was 80mm in diameter and 50mm in height. Pure water was added to the culture dish to 19mm from the edge. The schematic diagram of the test device assembly is shown in Fig.10 ; Then, place the test block and culture dish assembly together in a Q-SUN xenon lamp aging test chamber. The relative humidity should be maintained at 50±2%, and the temperature condition is 23-26.7℃. The total weight of the assembly is weighed every 24 hours and the periodic change of its water permeability is calculated. The test is conducted for a total of 28 days, and parallel samples are tested simultaneously in the same environment.
[0066] The water permeability test results of Examples 1-9 and the control sample blocks are shown in Table 4. In terms of the stable water permeability period of the test blocks (the water permeability value remains stable), the water permeability plateau period of the control sample test blocks is 12 days; the water permeability plateau period of the test blocks when the brick powder addition amount is 5%, 10%, and 15% is 11 days, 8 days, and 5 days respectively, and the water permeability plateau period gradually shortens with the increase of its content; when volcanic ash is used as an admixture, the effect of different volcanic ash addition amounts on the water permeability plateau period of the test blocks is not significant; the addition amount of fly ash in the test blocks has a significant effect on the water permeability period of rammed earth, and the water permeability period of the test blocks when the addition amount is 5%, 10%, and 15% is significantly shortened with the increase of its content, which is 9 days, 5 days, and 3 days respectively. Among different control groups, the overall water permeability period of the test blocks when fly ash is used as an admixture is relatively short.
[0067] In terms of the change in water permeability of the test blocks within a single day, the different components and contents of the admixtures lead to large differences in water permeability between individual test blocks. When the water permeability of the test blocks reaches the plateau, the order of water permeability within a single day is as follows: test blocks with 15% fly ash addition, test blocks with 10% fly ash addition, test blocks with 15% brick powder addition, test blocks with 10% brick powder addition, control test blocks, test blocks with 5% brick powder addition, and test blocks with 15% volcanic ash addition. The water permeability of the test blocks with 5% volcanic ash addition and 5% fly ash addition is close to that of the control sample, and the water permeability of the test blocks with 10% volcanic ash addition is close to that of the test blocks with 5% brick powder addition. When brick powder and fly ash are used as admixtures, the water permeability within a single day shows an upward trend with the increase of their content, while the water permeability within a single day gradually decreases with the increase of volcanic ash addition.
[0068] In terms of water permeability, the control sample has a water permeability of 5.17 gm -2 h -1Among all the rammed earth specimens with different admixtures, the water permeability of the rammed earth was the highest when the volcanic ash addition was 15%, which was about twice that of the control sample ( Fig.11 ).
[0069] Table 4 Water permeability test results of Examples 1-9 and control samples
[0070]
[0071]
[0072] Salt corrosion resistance test:
[0073] After curing for 20 days under standard conditions, the test blocks with a size of 50×50×50mm were taken out for testing. The test blocks prepared in Examples 1-9 and the control samples were immersed in a 14% NaCl solution by mass, so that the area below the height of 3mm of the test blocks was immersed in the solution. The immersion time for a single test was about 24 hours. After each immersion, the test blocks were dried at 40°C for 24 hours. The weight of the test blocks was weighed before and after drying, and their appearance was recorded by taking photos. The above test cycle test was carried out until the test blocks were destroyed. Parallel samples were carried out simultaneously in the same environment. The test time was 22 days. The immersion and drying steps were repeated 11 times during the test process. The test steps are shown in Fig.12 .
[0074] The test results on the 6th day are as follows Fig.13 As shown in the figure, it can be seen that the rammed earth test blocks with different admixture contents all showed salt analysis phenomenon. Compared with the control sample, the amount and rate of salt analysis in the test blocks showed an upward trend with the increase of brick powder content, among which the test blocks with 15% brick powder addition were similar to the control sample; with the increase of volcanic ash addition, the surface area of salt analysis in the test blocks showed a slight downward trend, but the overall change difference was not large, among which the surface area of salt analysis in the test blocks with 5% volcanic ash addition was close to the control sample; when the admixture was fly ash, the different addition amounts led to obvious differences in the test results. With the increase of fly ash content, the surface area of salt analysis in the test blocks showed a downward trend, among which the surface area of salt analysis in the test blocks with 5% fly ash addition was close to the control sample. When the test was carried out to the 8th day, the test blocks of the control sample began to show local cracks, and the cracking state was seen Fig.14 .
[0075] As time goes by, when soaking in salt water for 12 to 20 days, if Fig.15As shown, a large amount of salt is concentrated in the upper part of the test block accompanied by slight cracking, and material shedding, hollowing, peeling and other phenomena begin to appear in the lower part of the test block. There is no obvious difference in the above phenomena between the test blocks with different brick powder addition amounts, and the damage is more serious than that of the control sample; the damage of the test blocks with volcanic ash as an admixture is improved compared with brick powder, and the degree of damage tends to slow down with the increase of the addition amount; there is a significant difference in the degree of damage between the test blocks with different fly ash addition amounts, and the degree of damage of the test blocks decreases significantly with the increase of the addition amount. Among them, Fig.13 and Fig.15 The blue dashed line in the middle represents the interface analyzed by the test block salt. Fig.15 The orange dotted line in the middle is the hollowing / powdering boundary of the specimen.
[0076] The salt corrosion condition of the test block was observed until the 22nd day, when the test was terminated, and the degree of salt corrosion of the test block was presented in different colors. The evaluation of the salt corrosion condition of the test block is shown in Table 5. The control sample and the test blocks with 10% and 15% brick powder addition were seriously damaged. In addition to obvious hollowing and peeling on the surface of the test blocks, there were also serious material shedding and damage. The salt corrosion resistance of the test blocks with 5% brick powder and volcanic ash addition was improved compared with the control sample, but there were still obvious surface hollowing, peeling and powdering. With the increase of volcanic ash addition, the salt corrosion of the test blocks gradually decreased. The test blocks with 10% and 15% volcanic ash addition and 5% fly ash addition only had surface peeling. The test blocks with 10% and 15% fly ash addition were in good condition without obvious damage. Among them, green in the table indicates that the test block is in good condition; yellow indicates that the test block has slight peeling on the surface; orange indicates that the test block has hollowing and peeling on the surface; red indicates that the test block is severely damaged and is broken or disintegrated.
[0077] Table 5 Evaluation of salt corrosion of test blocks
[0078]
[0079] In summary, the modified rammed earth material prepared by the present invention has greatly improved mechanical properties (compressive strength, microstructure) and durability (water resistance, salt corrosion resistance, water permeability) compared with the control sample. Specifically, in terms of compressive strength, when the brick powder addition amount is 5%, the compressive strength is increased compared with the control sample; when the admixture is volcanic ash, the compressive strength of the test blocks with different volcanic ash addition amounts is significantly improved; when the admixture is fly ash, the compressive strength of the test blocks in different control groups is also significantly enhanced; overall, the compressive strength of the test blocks with 5% volcanic ash addition and 15% fly ash addition is the best, which is about twice that of the control sample. In terms of microstructure, compared with the control sample, rammed earth with different admixtures and addition amounts shows different degrees of optimization trends in structural density, and with the increase of their addition amount, the structural density gradually increases. In terms of water resistance, the rammed earth with brick powder as an admixture has poor water resistance, and its water resistance is better than that of the control only when the addition amount is 5%; when volcanic ash is used as an admixture, the water resistance of the test blocks with different volcanic ash addition amounts shows an increasing trend, but the trend is not obvious; when fly ash is used as an admixture, with the increase of fly ash addition, the water resistance of the test block gradually increases, and when the fly ash addition amount is 15%, the water resistance of the test block is the best, specifically: the water absorption rate of the modified rammed earth with 15% fly ash addition is about 1 / 4 of that of the control, and the water absorption extreme value is about 1 / 7 of the control. In terms of water permeability, compared with the control sample, the water permeability of the test block is enhanced when the brick powder addition is 10% and 15%; when volcanic ash is used as an admixture, the water permeability of the test block decreases; when fly ash is used as an admixture, the water permeability rate of the test block with 5% fly ash addition does not change much, and the water permeability of the test block with 10% and 15% fly ash addition is significantly enhanced, and the water permeability of the test block with 15% fly ash addition is the highest, about 2 times that of the control sample. In terms of salt corrosion resistance, compared with the control sample, the salt corrosion resistance of all modified rammed earth has different degrees of enhancement effect; among them, the test blocks with 5% and 10% brick powder addition, 10% and 15% volcanic ash addition, and 10% and 15% fly ash addition have significant effects, and the test block with 15% fly ash addition has the strongest salt corrosion resistance.
[0080] It should be noted that Photoshop CC 2018 was used for background removal and typesetting during the curing stage of the test blocks in this scheme; SPSS25 was used for statistical analysis of the compressive performance test data, and GraphPad Prism 7.0 was used for other statistical analyses; SPSS25 was used for statistical analysis of the water immersion resistance test data, and GraphPad Prism 7.0 was used for other statistical analyses. In addition, the two samples were further compared using a two-tailed Student's t-test, and the data were expressed as mean ± standard error, with p < 0.05 indicating a significant difference; SPSS25 was used for statistical analysis of the water permeability test data, and GraphPad Prism 7.0 was used for other statistical analyses; Photoshop CC 2018 was used for image processing of the salt corrosion resistance test results.
[0081] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A modified rammed earth material, characterized in that: The following raw materials are included in volume: 45 parts of yellow mud, 12 parts of sand, 7 parts of slaked lime, 2 parts of oyster shell ash, 1 part of glutinous rice flour, 5-15 parts of admixtures and 20% by mass of brown sugar water; The admixture is at least one of volcanic ash, brick dust and fly ash.
2. The modified rammed earth material according to claim 1, characterized in that: When the admixture is pozzolan, its volume is 5-15% of the volume of all raw materials.
3. The modified rammed earth material according to claim 1, characterized in that: When the admixture is brick powder, its volume is 5-15% of the volume of all raw materials.
4. The modified rammed earth material according to claim 1, characterized in that: When the admixture is fly ash, its volume is 5-15% of the volume of all raw materials.
5. The modified rammed earth material according to claim 2, characterized in that: The volume of the pozzolan is 10% of the volume of all raw materials.
6. The modified rammed earth material according to claim 3, characterized in that: The volume of the brick powder is 5% of the volume of all raw materials.
7. The modified rammed earth material according to claim 4, characterized in that: The volume of the fly ash is 15% of the volume of all raw materials.
8. A method for preparing the modified rammed earth material according to any one of claims 1 to 7, characterized in that: The steps include: The following raw materials are mixed evenly in volume: 45 parts of yellow mud, 12 parts of sand, 7 parts of slaked lime, 2 parts of oyster shell ash, 1 part of glutinous rice flour, 5-15 parts of admixtures and an appropriate amount of 20% by mass of yellow sugar water to obtain modified rammed earth material; wherein the admixture is at least one of volcanic ash, brick powder and fly ash.
9. The preparation method according to claim 8, characterized in that: When the admixture is pozzolan, its volume is 5-15% of the volume of all raw materials; when the admixture is brick powder, its volume is 5-15% of the volume of all raw materials; when the admixture is fly ash, its volume is 5-15% of the volume of all raw materials.
10. Use of the modified rammed earth material according to any one of claims 1 to 7 or the modified rammed earth material prepared by the preparation method according to any one of claims 8 to 9 in rammed earth buildings.